What Next After GAS and PANDA? - Ing, Caleb (J Neurosurg Anesthesiol, 2016)
On April 16(th) and 17(th), 2016, the Fifth biennial Pediatric Anesthesia & Neurodevelopment Assessment (PANDA) symposium was convened at the Morgan Stanley Children’s Hospital of New York at Columbia University Medical Center. During the symposium, experts in the fields of anesthesiology, neuropsychology, and epidemiology were convened in a small group session to determine the level of confidence in the current clinical evidence and the next steps in anesthetic neurotoxicity clinical research. Among the participants in the discussion, there remained a lack of consensus on whether anesthetic exposure causes long-term neurodevelopmental deficits in children based on the current evidence. This causal relationship between anesthesia exposure and neurodevelopmental deficit is difficult to establish using observational data, and current and future clinical trials are critical for answering this question. It was however recognized that the continuum of data that is seen in studies of other toxic environmental exposures, such as lead poisoning, has not been established in the anesthetic neurotoxicity literature, specifically regarding the timing of the exposure, the dose effects, contributing perioperative conditions, or vulnerable populations. As a result, these questions may need to be addressed in observational studies in order to guide future clinical trials.